Upaya Meningkatkan Profesional Guru dalam Menggunakan Model Pembelajaran Problem Centered Learning (PCL) pada Mata Pelajaran Matematika - Izmatul Husna (Publikasi Indonesia, 2023)
Being a professional teacher is not easy, because it requires special abilities, expertise in the field of teaching, so that he is able to carry out his duties and functions as a teacher with maximum ability. The phenomenon in the field, found that the professional ability of teachers is still very concerning, teachers find it difficult to develop varied learning methods in the classroom. One of these efforts is to conduct School Action Research which aims to improve the ability of teachers to teach their students in Mathematics subjects through the Problem Centered Learning (PCL) Learning Model. The implementation was carried out at SDN 23 Mato Aia, Sungai Pagu District, South Solok Regency. This study aims to find out whether through intensive coaching at KKG can overcome teacher problems in using the Problem Centered Learning (PCL) Learning Model in Mathematics subjects. Action hypothesis that intensive coaching in KKG can improve teachers' ability to use the Problem Centered Learning (PCL) Learning Model in Mathematics subjects in target schools. This research was conducted from July to December 2022 specifically for teachers at SDN 23 Mato Aia, Sungai Pagu District, Kabuapten, South Solok with 10 teachers. The instruments used are: (1) Observation of the teacher's ability to design lesson plans; (2) observation of the teacher's ability to carry out learning; (3) observation sheet of teacher creativity in the use of the Problem Centered Learning (PCL) Learning Model. From the results of the study, it can be concluded that the Articulation Learning Method can improve teachers' professional abilities in designing and implementing learning, where in the first cycle only 30% of teachers understand the Problem Centered Learning (PCL) Learning Model, in the second cycle it increases to 60% and in the third cycle it increases to 90%, with an increase in teacher understanding of the use of the Problem Centered Learning (PCL) Learning Model in learning In the end, an effective, active, and creative and fun learning atmosphere will present itself, so that student learning outcomes can improve.